Religious or Spiritual Experiences and Bipolar Disorder: A Case Study from the Perspective of Dialogical Self Theory - Ouwehand, Eva (Religions, 2020)
In this article, a case study will be presented of a person with bipolar I disorder, who struggles to interpret his religious experiences and how they are related to the disorder. The analysis builds on a larger study into religious experiences within the context of bipolar disorder (BD). In this previous study, medical and religious explanatory models for religious experiences related to BD often appeared to go hand in hand in patients who have had such experiences. In this case study, the various ‘voices’ in the interpretation process over time will be examined from the perspective of the dialogical self theory of Hubert Hermans, in order to explore the psychological dimension of this process. The case study demonstrates that a ‘both religious and pathological’ explanatory model for religious experiences consists of a rich and changing variety of I-positions that fluctuate depending on mood episode. Structured reflection from a spiritual and from a medical perspective over the course of several years helped this person to allow space for different dialoguing ‘voices’, which—in this case—led to a more balanced attitude towards such experiences and less pathological derailment. The systematic reflection on religious experiences by the person in the case study was mainly conducted without help of mental health care professionals and was not derived from a DST perspective. It could be argued, however, that DST could be used as a helpful instrument for the exploration of both medical and spiritual ‘voices’ in the interpretation of religious experiences in both clinical practice by hospital chaplains and by other professionals.